Media accountability and the new technology - Sorariba Nash (Asia Pacific Network, 1996)
Mass media in the Asia-Pacific region need to reexamine their old habits, beliefs and practices and ask: are we meeting the demands of the changing times? Or are we still capable of accommodating these changes? If not, what do we need to do?